Biophysical characteristics of Wosi Watershed area in Manokwari Regency, Indonesia - Mahmud; Abdul Aziz; Danang Wijaya; Wahyudi; Bambang Nugroho; Denisa Melanesia (Pusat Penelitian Lingkungan Hidup, IPB (PPLH-IPB) dan Program Studi Pengelolaan Sumberdaya Alam dan Lingkungan, IPB (PS. PSL, SPs. IPB), 2023)
Flood is number one Indonesian natural disaster in the last 10 years and its occurrence at Manokwari is frequently reported. Biophysical condition is playing a key role in carrying capacity of this catchment area.This study is to determine biophysical characteristics of Wosi Watershed to manage and mitigate flooding in Manokwari. Spatial analysis and field observation methods were used to collect the data. Biophysical variables are rainfall, watershed morphometric, slope, and land used. Carrying capacity is measured using flow regime coefficient and annual flow coefficient. The results showed that the heavy rainfall (> 100 mm) throughout the ten years with 10.5 wet months at average resulting very wet tropical climate. This watershed has an area of 2,346.32 ha, its circumference of 29.95 km2 with river length of 8.38 km resulting 0.33 (triangle) and 1.027 (triangle) for Rc and Re, respectively. This morphometry is rectangular and slightly oval(triangular) formed of four rivers with drainage pattern of dendritic, which resembles the shape of a tree branch/twig. Steep slopes are dominant (58.5%), with non-forest area (62%) of the flat and steep slope for settlement (698 ha), and flat slope for mixed dry farming (707 ha). From 2016-2020, river water flow changes rapidly from low to very high to generate flooding, but the carrying capacity is sometime changeable from good to bad. Water drainage, retaining walls, replantation, early warning system, and flooding leaflets mitigation campaign, are structural and non-structural mitigation could be parallelly conducted to manage and mitigate the flooding risks in future.